Enhancing Arabic Writing Proficiency through Genially-Based Differentiated Learning - Anisah Firdausi Nuzula; Maftukh Ghulam Mursyidan; Muhammad Baihaqi (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study examines the effectiveness of Genially-based differentiated learning in enhancing students’ Arabic writing proficiency. Using a quantitative pre-test and post-test design, the research involved seventh-grade students at MTsN 4 Sidoarjo. Differentiated instruction was applied by adjusting content, process, and product based on students’ learning styles—visual, auditory, and kinesthetic—through Genially’s interactive features such as multimedia presentations, quizzes, and animations. Data were collected via observation, interviews, documentation, and writing tests, and analyzed using paired-sample t-test and N-Gain calculations. The results showed a significant improvement in writing performance, with the average score rising from 62 to 85 and an N-Gain value of 0.61 (moderate–high). Students demonstrated better paragraph organization, idea development, vocabulary use, and grammatical accuracy, along with increased motivation and confidence. The study concludes that integrating Genially into differentiated learning effectively accommodates student diversity and improves Arabic writing skills. This approach aligns with the Independent Curriculum (Kurikulum Merdeka), emphasizing adaptive, student-centered, and technology-based learning. Teachers are encouraged to optimize digital media to create engaging, personalized, and future-oriented Arabic instruction